PENENTUAN KOEFISIEN TANAMAN MENGGUNAKAN DATA PENGAMATAN IKLIM DAN INDEX VEGETASI DARI SETELIT NOAA/ AVHRR - Eleonora Runtunuwu (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2007)
One of the most important parameter of climatic water balance computation is crop coefficient (Kc). Unfortunately, the Kc is one of the most difficult parameter to measure in the field. This paper attempts to determine the crop coefficient by using climate observation data and the NDVI (Normalized Difference Vegetation Index) derived from NOAA (National Oceanic and Atmospheric Administration). Calculation using Morton’s Complementary Relationship Areal Evapotranspiration (CRAE) method that used elevation (m), annual precipitation (mm), monthly air temperature ( C), sunshine duration (%), as minimum requirement data, has been applied for more than 900 climatic stations over the Asian region that well documented by FAO-CLIM agroclimatic database to obtain the Kc value. The result was then related to NDVI derived from spectral reflectance of NOAA/AVHRR data. The relation results of NDVI and crop coefficient gave significant linear equation as Kc = 0.08 + 1.83 NDVI, with average correlation coefficient 0.72. It was high over humid area such as in Java island of Indonesia; on the other hand, it was low in semi arid area, such as west part of India. Even the results above were fit only for a specified area; this study has demonstrated a potential use of NOAA image for supplying the crop coefficient value that would be particularly necessary to determine actual evapotranspiration.